Elevated atmospheric CO2 concentration and irrigation management during rice and red rice growth on post-harvest grain quality - Andrisa Balbinot; Tamara Heck; Anderson da Rosa Feijó; Marcus Vinícius Fipke; Gustavo Heinrich Lang; Cristiano Dietrich Ferreira; Maurício de Oliveira; Edinalvo Rabaioli Camargo; Luis Antonio de Avila (Ciência Rural)
ABSTRACT: The increase in atmospheric carbon dioxide concentration ([CO2]) can impact global food security. There are several rice types; the most consumed is white rice, and interest in pigmented rice is growing due to its health benefits. This study evaluated the effect of increasing [CO2] and different irrigation management on rice and pigmented (red) rice grain quality. Two-year experiments were conducted in an Open-Top-Chamber to investigate the effect of CO2 levels (400 and 700 μmol mol-1) and irrigation regimes (continuous and intermittent floods) in white rice cultivar and red rice in grain quality and physicochemical characteristics, protein, and phenolic compounds. Elevated [CO2] affected the white rice’s nutritional parameters, decreasing head rice yield and increasing chalk area, decreasing crude protein, and reducing textural profile parameters such as hardness, chewiness, and gumminess. Contrasting with the adverse effects of white rice quality, the red rice grown under high [CO2] changed only the variable amount of phenolics, producing greater amounts of phenolic compounds, a desirable nutritional characteristic. Irrigation management did not alter the nutritional quality of rice. This indicates that increased [CO2] positively affects red rice and adversely impacts white rice quality, depending on the rice grain’s cultivars and use.